They planted the Cape (Historia, 2021)
When Jan van Riebeeck, commanding a party of a hundred and twenty-six people, first set foot upon the shores of Table Bay in April 1652, the Directorate of the Dutch East India Company had already been assured that the soil of the place was as good as anywhere in the world, and that every product necessary to the refreshmen~ of the Company's fleets, and the support of a garrison, would grow. Their assurance derived from the experjences of the crew of the "Niewe Haerlem", one of the Company's return ships from its residency in Batavia (Java) of the year 1647, which in March of that year was blown ashore near the mouth of the Salt River in Table Bay. The com. mander of a sister ship left sixty of the "Haerlem's" crew, under the command of the junior merchant Leendert Janz, to salve the cargo, and to await the return fleet of the following year to pick them up and the salvage with them.
Keywords: Agriculture; Farming; Dutch East India Company; Labour